IMMUNOPATHOLOGY OF LYMPHOCYTIC CHORIOMENINGITIS VIRUS INFECTION OF NEWBORN MICE : ANTITHYMOCYTE SERUM EFFECTS ON GLOMERULONEPHROTIS AND WASTING DISEASE - Hirsch, Martin S. (The Rockefeller University Press, 1968)
Antithymocyte serum, when administered neonatally to mice, delayed the maturation of the lymphoid system, permitting development of cellular tolerance to LCM virus at an older age than is ordinarily possible. Humoral antibody formation was not prevented and the animals exhibited the paradox of high titers of both circulating virus and antibody. This, in turn, was followed by a chronic immunopathologic glomerulonephritis in most animals. Some animals developed wasting disease between 1 and 2 months of age, characterized by reticular cell hyperplasia and widespread infiltration into tissues and organs.